ANALYZING THE EFFECTS OF SUB-LETHAL DOSES OF CHLORPYRIFOS AND FOSETYL-ALUMINUM ON HEMATOLOGICAL AND BIOCHEMICAL PARAMETERS IN JAPANESE QUAIL (COTURNIX JAPONICA) - Mudassar Maqbool, Ahmad Ali, Zian Ul Abideen, Tahira Ruby, Tayyaba Khan, Wajeeha Afzal, Sidra Bashir, Sobia Malik, Sheikh Muhammad Azam, Mehroz Ali; Tehseen Abbas, Aziz Ullah, Faiza Waheed, Hafiz Muhammad Sajawal, Hira Gill, Muhammad Zeshan Haider, Sobia Abid (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Chlorpyrifos and Fosetyl-Aluminum are widely used pesticides in agriculture for controlling insects and fungi, respectively. Hematological and biochemical parameters serve as optimal biomarkers to determine physiological and chemical alterations. To analyze the possible toxicological effects on the hematology and biochemistry of Japanese Quail (Coturnix japonica), Chlorpyrifos and Fosetyl Aluminum were used to understand the potential risks posed by these chemicals to avian species. Adult male birds (n=30), 4-6 weeks old, weighing between 90-100g were randomly divided into 5 groups; (G1) Control (Untreated), treatment groups (G2, G3) were given (0.01 mg/day) as low dose while (G4, G5) were given (0.02 mg/day) as high dose of chlorpyrifos and fosetyl aluminum. On the 10th, 15th, and 20th day of the experiment, quails were slaughtered for blood collection. After 10 days of exposure to chlorpyrifos, notable dose-dependent changes were observed in urea, creatinine, bilirubin, ALT, ALP, WBC, MCV, and granulocyte percentages. By 15 days, additional significant increases were noted in MCH and lymphocyte percentages, while parameters such as RBC count, HCT, MCHC, and platelet count remained unaffected. After 20 days, these trends continued with significant elevations in urea, creatinine, bilirubin, ALT, ALP, WBC, MCV, MCHC, lymphocyte, and granulocyte percentages particularly at higher doses. Similarly, after 10 days of Fosetyl-Aluminum exposure, there were significant increases in urea, creatinine, ALT, ALP, WBC, MCHC, granulocyte percentage, and platelet count, with no significant differences in bilirubin, RBC count, HCT, MCV, MCH, and lymphocyte percentage. By 15 days, additional significant increases were observed in bilirubin, MCV, MCH, MCHC, and lymphocyte percentage, while RBC count, HCT, and platelet count remained unaffected. After 20 days, these trends continued with significant elevations in urea, creatinine, bilirubin, ALT, ALP, WBC, MCV, MCHC, lymphocyte, and granulocyte percentages, with no significant changes in RBC count, hematocrit, and platelet count. These findings provide understanding of the multifaceted effects of treatment and time on liver, kidney, immune, and hematological functions. Further research is required to understand the mechanisms and clinical significance of these impacts on health of Japanese Quail.